2020
DOI: 10.1159/000512119
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Vascular Accesses in Chronic Hemodialysis Patients

Abstract: <b><i>Background/Aims:</i></b> Vascular access (VA) is the highest risk factor for blood infections, hospitalization, and mortality of patients undergoing hemodialysis (HD). The risk of mortality while using a catheter is greater than that while using grafts. The objective of this article is to know the survival rate in relation to the type of VA. <b><i>Methods:</i></b> A retrospective cohort of HD patients was studied. The data gathered included age, gender, fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In a cohort of 5,466 patients, the survival rate at 5 years was 48% in central venous catheter (CVC) patients, including TCCs and non-tunneled catheters A recent study reported that the survival of CVC-Tuff in 1 ear was 93.59% [8]. Our data showed that the 1-year and 5-year survival rates of TCCs were 97.3% and 43.3%, respectively, which is consistent with results of the above two studies [7,8]. Min et al [9] showed a median survival time of 45.0 (95% CI, 29.3-69.7) months for TCCs, which differs from 2) in the study by Min et al [9], the average age of HD patients was 68.6 ± 14.6 years and diabetes was observed in 35.6% of the patients, whereas our data showed an average age of 65.0 ± 15.5 years, with diabetes in 25.3% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a cohort of 5,466 patients, the survival rate at 5 years was 48% in central venous catheter (CVC) patients, including TCCs and non-tunneled catheters A recent study reported that the survival of CVC-Tuff in 1 ear was 93.59% [8]. Our data showed that the 1-year and 5-year survival rates of TCCs were 97.3% and 43.3%, respectively, which is consistent with results of the above two studies [7,8]. Min et al [9] showed a median survival time of 45.0 (95% CI, 29.3-69.7) months for TCCs, which differs from 2) in the study by Min et al [9], the average age of HD patients was 68.6 ± 14.6 years and diabetes was observed in 35.6% of the patients, whereas our data showed an average age of 65.0 ± 15.5 years, with diabetes in 25.3% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 5,466 patients, the survival rate at 5 years was 48% in central venous catheter (CVC) patients, including TCCs and non-tunneled catheters [ 7 ]. A recent study reported that the survival of CVC-Tuff in 1 ear was 93.59% [ 8 ]. Our data showed that the 1-year and 5-year survival rates of TCCs were 97.3% and 43.3%, respectively, which is consistent with results of the above two studies [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some reports suggest that CVC is associated with a higher mortality risk than AVF. It is worth mentioning that the survival of patients with stage 5 CKD has improved considerably over the years (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%